Free Vascularized Fibular Graft for Reconstruction of the Lateral Clavicle: A Case Report and Review of the Literature. Issue 4 (October 2019) - Arenas-Miquelez, Antonio; Karargyris, Orestis; Olariu, Radu; Zumstein, Matthias
Abstract : Case: A 50-year-old female patient presented with significant (40%) bone loss of the lateral clavicle extending to the acromioclavicular (AC) joint, as a result of multiple, failed revision surgeries following a fracture-dislocation. She was treated with a free vascularized fibular graft and biplanar stabilization of the AC joint. At 4 years of follow-up, the patient had experienced resolution of painful symptoms with a Constant-Murley score of 72. Conclusions: Reconstruction of large, lateral clavicle defects with a free vascularized fibular graft and biplanar stabilization of the AC joint may provide a satisfactory clinical outcome.